Efficacy and safety of neoadjuvant immunotherapy combined with chemoradiotherapy or chemotherapy in esophageal cancer: A systematic review and meta-analysis - Liu, Yunsong; Bao, Yongxing; Yang, Xu; Sun, Shuang; Yuan, Meng; Ma, Zeliang; Zhang, Wanting; Zhai, Yirui; Wang, Yang; Men, Yu; Qin, Jianjun; Xue, Liyan; et al. (Frontiers in Immunology, 2023)
Background Significant progress has been made in the investigation of neoadjuvant immune-chemoradiotherapy (NICRT) and neoadjuvant immune-chemotherapy (NICT) on the outcomes of esophageal cancer patients. To summarize the current developments, a systematic review and meta-analysis were conducted to evaluate the efficacy and safety of neoadjuvant immunotherapy combined with chemoradiotherapy or chemotherapy. Methods A search strategy of prospective studies on esophageal cancer receiving neoadjuvant immunotherapy was predefined to scan PubMed, Embase, Cochrane, and additional major conferences for prospective studies. Efficacy was assessed by pathological complete response (pCR), major pathological response (MPR), and R0 resection rates. Safety was evaluated based on the incidence of grade ≥ 3 treatment-related adverse events (TRAEs), neoadjuvant therapy completion rate, surgical resection rate, and surgical delay rate. Differences between the NICRT and NICT groups were also analyzed. Results A total of 38 studies qualified for the analysis. The pooled pCR, MPR, and R0 resection rates were 30, 58, and 99%, respectively. The pCR and MPR in the NICRT vs. NICT group were 38% vs. 28% (p=0.078) and 67% vs. 57% (p=0.181), respectively. The pooled incidence of grade ≥ 3 TRAEs was 24% (NICRT,58%, I2 = 61% vs. NICT,18%, I2 = 79%; p<0.001). In addition, the pooled neoadjuvant therapy completion and surgical resection rates were 92% and 85%, respectively; the difference was not statistically significant between the NICRT and NICT groups. Conclusions Neoadjuvant immunotherapy combined with chemoradiotherapy or chemotherapy is effective and safe in the short term for locally advanced esophageal cancer. However, further randomized trials are needed to confirm which combined model is more favorable. Systematic review registration https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42021284266, identifier CRD42021284266.